CD83: Activation Marker for Antigen Presenting Cells and Its Therapeutic Potential - Li, Ziduo; Ju, Xinsheng; Silveira, Pablo A.; Abadir, Edward; Hsu, Wei-Hsun; Hart, Derek N. J.; Clark, Georgina J. (Frontiers in Immunology, 2019)
CD83 is a member of the immunoglobulin (Ig) superfamily and is expressed in membrane bound or soluble forms. Membrane CD83 (mCD83) can be detected on a variety of activated immune cells, although it is most highly and stably expressed by mature dendritic cells (DC). mCD83 regulates maturation, activation and homeostasis. Soluble CD83 (sCD83), which is elevated in the serum of patients with autoimmune disease and some hematological malignancies is reported to have an immune suppressive function. While CD83 is emerging as a promising immune modulator with therapeutic potential, some important aspects such as its ligand/s, intracellular signaling pathways and modulators of its expression are unclear. In this review we discuss the recent biological findings and the potential clinical value of CD83 based therapeutics in various conditions including autoimmune disease, graft-vs.-host disease, transplantation and hematological malignancies.